Treating hazardous locations at federal route 50 - Mustakim, Fajaruddin (2005)
Total number of road accident in Malaysia exceeded 299,305 in year 2003 alone. Average person died from this road accident every single day were 16 persons. Lack of attention, reckless driving, lack of proper protection, speeding and bad personal habit are some of the problems that cause accident. Federal Route 50 from Batu Pahat – Ayer Hitam experience 3,937 road traffic accident from year 2000 to 2004, of these 1,160 were casualty accidents. These accidents killed 116 people and injuring 1,044 people. This research was undertaken to identify factors that may contribute to the cause of accidents and to propose improvement at the selected location in order to reduce the accident rate. In this study, Pintas Puding KM20 was selected as the study section based on the blackspot ranking. The road accident trends and blackspot ranking were established at Federal Route 50 (FT 50) Batu Pahat – Ayer Hitam. Statistical analysis, collision diagram, traffic studies and spot speed studies were carried out for greater understanding of the problem. Skid Resistance Test were also conducted at Section 19(KUiTTHO and Fujitsu factory), Section 20 (Pintas Puding) and Section 21 (Taman Maju and Taman Sri Raja). The result showed that only skid resistance value (SRV) obtained at KUiTTHO traffic light was less than minimum skid resistance requirement. Further more, this study manage to develop the accident prediction model for Federal Route 50 by using Multiple Linear Regression. It also revealed that increase of the accident rates can be explained by either the rise in traffic volume, speed or number or access points.